Plasma Ceramides and Sphingomyelins of Pediatric Patients Increase in Primary Ciliary Dyskinesia but Decrease in Cystic Fibrosis. Issue 3 (2nd March 2020) - Bal Topçu, Dilara; Tugcu, Gokcen; Ozcan, Filiz; Aslan, Mutay; Yalcinkaya, Ahmet; Polat, Sanem Eryilmaz; Hizal, Mina; Yalcin, Ebru Elmas; Ersoz, Deniz Dogru; Ozcelik, Ugur; Kiper, Nural; Lay, Incilay; et al.
Abstract: We investigated plasma sphingomyelin (CerPCho) and ceramide (Cer) levels in pediatric patients with cystic fibrosis (CF) and primary ciliary dyskinesia (PCD). Plasma samples were obtained from CF ( n = 19) and PCD ( n = 7) patients at exacerbation, discharge, and stable periods. Healthy children ( n = 17) of similar age served as control. Levels of 16–24 CerPCho and 16–24 Cer were measured by LC–MS/MS. Concentrations of all CerPCho and Cer species measured at exacerbation were significantly lower in patients with CF than PCD. 16, 18, 24 CerPCho, and 22, 24 Cer in exacerbation; 18, 24 CerPCho, and 18, 20, 22, 24 Cer at discharge; 18, 24 CerPCho and 24 Cer at stable period were significantly lower in CF patients than healthy children ( p < 0.001 and p < 0.05). All CerPCho and Cer levels of PCD patients were significantly higher except 24 CerPCho and 24 Cer during exacerbation, 24 CerPCho at discharge, and 18, 22 CerPCho levels at stable period ( p < 0.001 and p < 0.05) compared with healthy children. There was no significant difference among exacerbation, discharge, and stable periods in each group for Cer and CerPCho levels. This is the first study measuring plasma Cer and CerPCho levels in PCD and third study in CF patients. The dramatic difference in plasma levels of most CerPCho and Cer species found between two diseases suggest that cilia pathology in PCD and CFTR mutation in CF seem to alter sphingolipid metabolism possibly in opposite directions.